Limitations of current screening methods for lipid disorders in Korean adolescents and a proposal for an effective detection method: a nationwide, cross-sectional study - Jung Hyun Shin; Ji In Cheong; Hee Won Cheuh; Jae-Ho Yoo (Korean Society of Pediatric Endocrinology, 2020)
Purpose To determine the limitations of current screening methods for lipid disorders and to suggest a new method that is effective for use in Korean adolescents. Methods Data from the 6th Korea National Health and Nutrition Examination Survey (2013-2015) were analyzed. The diagnostic validity (sensitivity and specificity) of various cardiovascular risk factors currently used for lipid disorder screening was investigated, as was the diagnostic validity of non-HDL-cholesterol ≥145 mg/dL as a screening tool. Results The prevalence of dyslipidemia and familial hypercholesterolemia (FH) among Korean adolescents was 20.4%±1.0% and 0.8%±0.3%, respectively. The current standard screening methods identified only 5.9%±1.4% and 30.3%±17.2% of the total number of dyslipidemia and FH cases, respectively. The diagnostic sensitivity and specificity of lipid profile analysis for dyslipidemia among obese adolescents were 19.5%±2.3% and 93.6%±0.8% and for FH were 30.3%±17.2% and 91.1%±0.8%, respectively. When adolescents with obesity, hypertension, or a family history of dyslipidemia or cardiocerebrovascular disease for over 3 generations were included in the screening, diagnostic sensitivity increased to 68.4%±2.8% for dyslipidemia and 83.5%±2.7% for FH. Universal screening of all adolescents based on non-HDL-cholesterol levels had sensitivities of 30.2%±2.7% and 100%, and specificities of 99.2%±0.3% and 94%±0.6% for dyslipidemia and FH, respectively. Conclusions New screening methods should be considered for early diagnosis and treatment of lipid disorders in Korean adolescents.